Exploring Language Boredom among Non-English Major Students in English Language Learning - Yue, Xinran (Transactions on Social Science, Education and Humanities Research, 2024)
This study investigates the phenomenon of boredom experienced by non-English major college students in their English language learning, aiming to provide valuable insights into the factors influencing boredom, such as language proficiency levels and gender. Additionally, it aims to guide educators in effectively addressing negative emotions and enhancing students’ efficiency in acquiring English skills. Employing quantitative research methods including surveys and statistical analysis, this study collects data on the frequency, intensity, triggers of English boredom, as well as its impact on academic performance. The data analysis reveals that non-English major students commonly experience feelings of boredom when studying English, particularly PowerPoint Presentation Boredom. There are variations in the causes of boredom among non-English major college students based on their language proficiency levels and gender. The findings indicate that students have grown weary of conventional approaches to grammar and vocabulary instruction, expressing a desire for more engaging and practical learning methods. Consequently, this study concludes that educators should embrace innovative pedagogical techniques such as gamification and task-based learning to invigorate students’ interest and motivation.